Fatores intervenientes no processo de busca e obtenção de informação em uma biblioteca universitária por usuários da área de odontologia - Cristiane Batista Bezerra Torres (2001)
Given the establishment of a new paradigm, the information society paradigm, according to which information is the mainspring of social transformation and technological advance, this study analyses the role of the university library in supporting academic activities such as teaching, research and service, specifically in the Health area. The academic Dentistry community feel the necessity of accessing current information in order to keep up with innovations from the most simple prevention procedures to the complexes rehabilitation treatments. Thus, the main objective of this study is to investigate what are the influential factors on the information-seeking and information-obtaining behavior of professors and undergraduate students of the Dentistry Course of Universidade Federal do Piauí (UFPI) in the Biblioteca Comunitária Jornalista Carlos Castello Branco (BCCB). The Dentistry Course of UFPI is the reference to local professionals and BCCB is the main library of the university. The data was collected by means of questionnaires, processed by Statistical Package for the Social Sciences (SPSS) and submitted to the Pearsons Chi-Square test. The questionnaires were structured into the following parts: (a) general characterization of the respondents; (b) information needs; (c) use of BCCB and (d) participation in user education programs. The results obtained show that the influential factors on information-seeking behavior of professors are: (a) low involvement with research; (b) inadequacy of BCCBs collection, specially the periodicals collection; (c) unawareness of the librarian as an information professional; (d) use of private libraries and informal information sources, such as consultation to colleagues or specialists in areas of interest; (e) preference for accessing on-line information at more convenient place; (f) unawareness of BCCBs products and services and (g) non-participation in user education programs. For undergraduate students, the influential factors are: (a) familiar income; (b) linguistic barrier; (c) unawareness of the librarian as an information professional; (d) inadequacy of BCCBs collection; (e) unawareness of BCCBs products and services and (f) non-participation in user education programs.